Incidencia del impuesto a la renta en el personal que labora bajo relación de dependencia en la Universidad Técnica de Cotopaxi del período 2021 – 2022 UISILÌ. - Guanotasig Guanoluisa, Yesenia Lizeth (2023)
The present research project was carried out with the title "Incidence of income tax on staff who work under a dependent relationship at the Technical University of Cotopaxi during the period 2021 - 2022" with the purpose of determining the effect generated by the reforms applied to the Ley de Régimen Tributario Interno (LRTI) in relation to income tax declarations and deduction of staff expenses for people who work under a dependency relationship, the methodology had a qualitative approach, which allowed the analysis and interpretation of data , the technique used to obtain information is the survey, it was applied to teaching and administrative staff who have a monthly salary of more than $1,000.00, obtaining a total population of 409 workers and a sample of 198 people, for a better understanding of the Staff that are part of the institution were classified according to the scale and their different levels, which allowed us to show an increase between 68% and 100% in the payment of income tax between 2021 and 2022 for teaching and administrative staff of the Technical University of Cotopaxi.